PELATIHAN ARTIFICIAL INTELLIGENCE DALAM MENDUKUNG LITERASI TEKNOLOGI INFORMASI PADA PEMBELAJARAN ABAD 21 DI MTS NURUL HUDA SITUBONDO - Zainur Rasyid Ridlo; Dwi Wahyuni; Silvi Putri Ayu Ningsih; Miranda Wulandari Rahmawati (STKIP PGRI SITUBONDO, 2025)
The objective of this community service activity is to enhance the information technology literacy of teachers and students at MTs Nurul Huda Situbondo through machine learning-based Artificial Intelligence (AI) training, with a focus on Convolutional Neural Network (CNN) implementation. The training program has been meticulously designed to introduce the fundamental concepts of artificial intelligence and its practical applications in various domains, with a particular emphasis on its impact on education and agriculture. The training method utilizes a hands-on approach through open-source AI applications, such as Google Teachable Machine. The participants were trained to construct rudimentary artificial intelligence (AI) models that were capable of performing face recognition, fruit quality classification, leaf disease identification, and plant species classification. The findings of this initiative have demonstrated a substantial enhancement in the information technology literacy dimension of the participants, as evidenced by an augmentation in conceptual comprehension, proficiency in utilizing AI technology, and a favorable disposition towards the integration of technology in educational pursuits. A significant outcome of this endeavor is the development of an AI model for disease classification on mango leaves. The efficacy of this training program substantiates the notion that technology-based learning methodologies can effectively cultivate 21st-century competencies, such as critical thinking, problem-solving, and digital proficiency. Furthermore, it fosters the development of an innovative and adaptable learning environment within the madrasah context.